Protein Quantitative Method Based on Determination of Amino Acid by LC-ID-MSLI - Yongli, GAO Yanqiu, XUE Minjie, HAO Yuhong, LI Jie (Journal of Isotopes, 2023)
In order to quantitate protein, a liquid chromatography-isotope dilution mass spectrometry method for the analysis of amino acids in protein hydrolysate was established. The protein was hydrolyzed at 130 ℃ in the presence of 6 mol/L hydrochloric acid solution, and separated by Hypercarb porous graphite carbon chromatography column and 0.1% perfluoropentanoic acid aqueous solution/acetonitrile mobile phase system. Five stable amino acids (proline, valine, leucine, isoleucine and phenylalanine) were selected for quantitative determination with their corresponding stable isotope markers as internal standard, and the absolute quantitative determination of protein was achieved by combining protein sequence information. The linear relationship of the five amino acids is good within the range of 10-1 000 ng/mL (R2>0.995), the limit of detection and the limit of quantification are between 0.02-0.07 ng/mL and 0.06-0.2 ng/mL, respectively. The recovery at three different levels is between 97.0%-102.4%, and the relative standard deviation is between 1.1%-3.0%. The analysis results of human IgG monoclonal antibody to nucleocapsid protein solution reference material of 2019 Novel Coronavirus and the measurement results of national metrological comparison of 2019nCovid nucleocapsid protein are satisfactory, which proves that the method has sufficient accuracy for protein determination.